Granular-free glass component ink applied to conductive paste / printing ink, preparation and application
By producing nano-scale glass phases in conductive pastes by particle-free glass component ink, the problem of high glass transition temperature and large particle size of glass powder in traditional conductive pastes is solved, and the generation of dense ohms at lower temperatures is achieved Contact improves the bonding force and conductivity between metal and substrate, simplifies the process and achieves green and environmentally friendly production.
Patent Information
- Application Number
- CN202411260574.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The high glass transition temperature and large particle size of glass powder in traditional conductive pastes limit their application range, resulting in high sintering temperature and poor ohmic contact between metal particles, affecting the conductivity.
Using particle-free glass component ink, a stable complex is formed through bismuth precursor and an amine complexing agent, a glass component containing silicon and boron is added, and dissolved in an organic solvent to form particle-free ink, used for Instead of some traditional glass powder, sintering at lower temperatures produces nano-scale glass phases, which are filled between metal particles and improve ohmic contact.
Deep ohmic contacts are generated at lower temperatures, improving the bonding force and conductivity between metals and substrates, reducing the impact of traditional large-grain glass melts on the intermetallic interface connectivity, simplifying the process and achieving green and environmentally friendly production.
Smart Images

Figure CN119286301A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive pastes, and in particular to a particle-free glass component ink applied to conductive pastes / inks, and its preparation and application. Background Art
[0002] Conductive paste is a commonly used functional material, widely used in photovoltaics, microelectronic packaging, sensors, displays, RFID and printed antennas, integrated circuit printing and other fields. In the production of crystalline silicon solar cells, silver-based conductive paste is used as the front electrode and back electrode (BSF or PERC structure back paste) to ensure efficient photocurrent collection and low contact resistance. Conductive paste also plays a key role in semiconductor packaging, especially in high-density interconnection technology and flip chip technology, used for screen printing to form reliable circuit connections and heat dissipation paths. Among them, silver / palladium paste is often used in the manufacture of internal electrodes of multilayer ceramic capacitors (MLCCs). In the manufacture of liquid crystal displays (LCDs) and organic light-emitting diodes (OLEDs), conductive paste is used to make transparent conductive electrodes, which can replace traditional indium tin oxide (ITO) electrodes, improve the stretchability of electrodes and reduce costs. With the rapid innovation and development of electronic, information and microelectronic technologies, electronic devices are developing towards environmental protection, integration and miniaturization, which places higher and higher requirements on the performance of conductive pastes. The development of new environmentally friendly electronic pastes with high performance and low cost has become a research hotspot.
[0003] Conductive paste is composed of conductive particles (such as precious metal powder, carbon-based nanomaterials, composite conductive particles, etc.), glass powder and organic carrier, wherein the glass powder is usually composed of low-melting-point inorganic oxides. During the subsequent sintering process of the conductive paste, the glass powder is heated and molten to wet the surface of the substrate, promoting the densification of the metal. After the molten glass powder is cooled, it forms a glass phase that fills between the metal particles, forming a dense metal film, which improves the mechanical strength and electrical properties of the metal circuit or electrode. During the sintering process, the molten glass powder adheres and penetrates into the surface of the substrate, and after cooling, it bonds the metal and the substrate, while reducing the difference in thermal expansion coefficients between the metal and the substrate, forming a firm connection between the metal and the substrate.
[0004] Most traditional conductive pastes use lead-containing glass powder as a binder, but lead is harmful to health and the environment, and the use and discharge of lead should be restricted. This makes the preparation of silver conductive paste with lead-free glass powder as the binder phase a research direction. Common lead-free glass powders are calcium oxide system, bismuth oxide system and aluminum oxide system. Among them, the glass transition temperature of calcium oxide system and aluminum oxide system glass powder is relatively high. The higher the temperature, the higher the cost, and the too high sintering temperature affects the integrity of the metal circuit after sintering. Bismuth oxide system glass powder usually has a relatively low melting point, and the glass transition can be completed at about 800°C, and it can form a strong connection with a variety of substrates. However, for some substrates that cannot withstand high temperatures, such as PVA, PET, PI and other polymers, irreversible damage will occur at this sintering temperature, which greatly limits the application range of conductive pastes.
[0005] In addition, the particle size of glass powder has a great influence on the performance of conductive paste. The oxide particles in the commonly used glass powder are made by mechanical crushing by ball milling and other methods, and are uniform particles with an average particle size of several microns. The average size of the glass melt contained in the conductive paste is relatively large. During sintering, it is filled between metals and between metals and substrates, making it difficult for the metals to form a continuous conductive path due to poor contact and metallization. "Jeon SJ, Koo SM, Am Hwang S. Optimization of lead-and cadmium-free front contact silver paste formulation to achieve high fill factors for industrial screen-printed Si solar cells [J]. Solar Energy Materials and Solar Cells, 2009, 93 (6-7): 1103-1109" studied the effect of the average particle size of glass powder on the conductivity of conductive paste. Solar cells made of paste with larger particles of glass powder have higher junction shunt and leakage rate. When using glass melt with smaller average size particles, the amount of glass powder can be reduced, and a higher fill factor and conversion efficiency can be obtained.
[0006] The main components of the particle-free glass phase ink proposed by the present invention are some low-melting-point organic solvents, bismuth-containing precursors and borosilicate-containing components, which can be decomposed at a relatively low temperature to produce glass phase components such as bismuth oxide. When the glass phase ink is added to the conductive paste, the glass phase material produced during the sintering process can bond the metal and the substrate, so that the metal and the substrate have ohmic contact, thereby improving the bonding force between the metal and the substrate and replacing the function of the traditional glass powder.
[0007] The glass phase ink proposed by the present invention is a particle-free type and does not contain large-particle oxide components. It replaces part of the traditional glass powder in a certain proportion and is added to the conductive paste and mixed evenly. During the sintering process, it is in-situ decomposed to generate nano-scale glass phase particles, which are filled between metal particles to make them dense. The small-particle glass phase can also reduce the influence of the traditional large-particle glass melt between metals on the interface connectivity between metal particles, thereby producing good ohmic contact and improving the conductivity of the metal. Summary of the invention
[0008] The present invention provides a method for preparing a particle-free glass component ink with a simple process and green environmental protection to solve the problems that the glass transition temperature of the traditional glass powder in the existing conductive paste is high, the sintering temperature of the conductive paste is high, resulting in limited application scenarios, and the glass powder particle size is large and affects the ohmic contact between metal particles after sintering. The ink is added to the existing conductive paste as a sintering aid to replace part of the glass powder, and can be sintered at a lower temperature to produce a glass phase component to bond the metal and the substrate, thereby improving the bonding force between the metal and the substrate. At the same time, the in-situ decomposition generates small particles of glass phase material to fill between micron-sized metal particles, thereby improving the adverse effects of large-particle glass melt in the traditional glass phase on the ohmic contact between metals.
[0009] In order to achieve the above-mentioned purpose, the main technical scheme adopted by the present invention is as follows: a particle-free glass component ink applied to conductive paste / ink, wherein the particle-free glass component ink adopts a bismuth precursor component and an amine complexing agent to form a stable complex, and then adds a glass component containing silicon and boron, dissolves it in an organic solvent and filters it to form a particle-free ink, and then adds it to a traditional conductive paste as a sintering aid; the particle-free glass component ink decomposes in situ during sintering to produce bismuth oxide, boron oxide, and silicon oxide, which are filled between metal particles and between the metal and the substrate, become molten during further heating, and produce dense ohmic contact after cooling and solidification.
[0010] Additives are added to the particle-free glass component ink to adjust its viscosity and leveling properties and adjust the glass phase transition temperature after the glass phase components are decomposed.
[0011] The particle-free glass powder ink has strong stability and no precipitation is generated when stored at room temperature for one month.
[0012] A method for preparing a particle-free glass component ink for use in conductive paste / ink comprises the following steps:
[0013] 1) The particle-free glass component ink is composed of the following components in percentage by mass: 20-50% bismuth precursor component, 1-20% boron and silicon-containing glass component, 10-20% amine complexing agent and 0.001-10% organic additive, and the rest is solvent; the amine complexing agent is fully dissolved in the solvent according to the above proportion, and then the bismuth precursor is added and stirred until completely dissolved to prepare a basic bismuth-based ink;
[0014] 2) adding a glass component containing boron and silicon to the bismuth-based ink prepared in step 1), and stirring at room temperature until the bismuth is completely dissolved;
[0015] 3) adding different additives to the ink prepared in step 2) in proportion to reduce the decomposition temperature of the ink and adjust the viscosity and surface tension of the ink; in various configurations, the additives are one or more of a viscosity regulator, a surface tension modifier, a film former, and a defoaming agent; stirring at room temperature for 1 to 10 hours until the ink is dissolved without particles, to obtain a glass component ink;
[0016] 4) The glass component ink prepared in step 3) is filtered through a 0.22 μm microporous filter membrane to obtain a particle-free glass component ink.
[0017] The bismuth precursor is various bismuth-containing organic substances; the solvent is a mixture of one or more organic solvents with a boiling point below 300° C. under normal pressure; the amine complexing agent is one or more of ammonia water, aliphatic amines, alcohol amines, amides, and aromatic amines; and the boron- and silicon-containing glass component is various boron- and silicon-containing organic substances.
[0018] The viscosity regulator is gum arabic, pectin, agar, gelatin, alginate, carrageenan, general gelatin or a polysaccharide derivative; the organic polymer viscosity regulator is a homopolymer or a copolymer; the defoaming agent is one or more of fluorosilicone, mineral oil, vegetable oil, polysiloxane, ester wax, fatty alcohol, glycerin, stearate, silicone and polypropylene polyether.
[0019] The ink is affected by different additives, and has a viscosity of 10 to 40 mPa·s and a surface tension of 5 to 40 mN / m.
[0020] The invention discloses an application of a particle-free glass component ink for conductive paste / ink, wherein the particle-free glass component ink is added to the conductive paste as a sintering aid; the prepared particle-free glass component ink is added to different conductive pastes at a volume fraction of 1 to 20%, and stirred for 1 hour to obtain a mixed ink with uniform components; the mixed ink is coated or printed on different substrates by dripping, dipping, spin coating or printing to form a layer or pattern, and the mixed ink is sintered by a certain method to obtain a metal film.
[0021] The substrate material is silicon, silicon carbide, quartz, glass, and ceramics; the sintering temperature ranges from 400 to 800° C., and the sintering time ranges from 10 minutes to 5 hours.
[0022] The conductive paste includes glass-based conductive paste and resin-based conductive paste; according to the classification of conductive functional phase fillers, the conductive paste includes carbon paste and various metal pastes.
[0023] The beneficial effects of the present invention are as follows: the particle-free glass component ink is added to the conductive paste as a sintering aid to replace part of the traditional glass powder, and can be decomposed at a relatively low temperature to generate glass components to connect the metal and the substrate. The particle-free glass component ink is added to the conductive paste to generate small particles of glass melt in situ during the sintering process, and after solidification, it is densely filled between the metal particles, reducing the influence of the traditional micron-level glass powder on the ohmic contact between the metals, and further improving the conductivity of the metal path after sintering. In addition, the preparation process is simple and green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the SEM image of the film after sintering the mixed ink in Example 3. DETAILED DESCRIPTION
[0025] The present invention provides a particle-free glass component ink, preparation and application. The particle-free glass component ink uses a bismuth precursor component and an amine complexing agent to form a stable complex, then adds a glass component containing silicon and boron, dissolves it in an organic solvent and filters it to form a particle-free ink, and then adds it to a traditional conductive slurry as a sintering aid. The ink decomposes in situ during sintering to produce bismuth oxide, boron oxide, and silicon oxide that fill the metal particles and between the metal and the substrate, and becomes a molten state during further heating. After cooling and solidification, it produces a dense ohmic contact, thereby improving its electrical properties and mechanical connection strength. Adding various additives to the ink can adjust its viscosity and leveling properties, adjust the glass phase transition temperature after the decomposition of the glass phase component, and improve its sintering aid performance. The new ink has strong stability and can be stored at room temperature for 1 month without precipitation. The preparation method is simple and easy to operate, low cost, green and environmentally friendly, and easy to realize industrial production.
[0026] The method for preparing the particle-free glass component ink comprises the following steps:
[0027] 1) The particle-free glass component ink of the present invention is composed of the following components in percentage by mass: 20-50% bismuth precursor component, 1-20% boron and silicon-containing glass component, 10-20% amine complexing agent and 0.001-10% organic additive, and the rest is solvent. First, the amine complexing agent is fully dissolved in the solvent according to the above ratio, and then the bismuth precursor is added to the mixed solution and stirred until it is completely dissolved to prepare a basic bismuth-based ink.
[0028] 2) Adding a glass component containing boron and silicon to the bismuth-based ink prepared in step 1), and stirring at room temperature until completely dissolved.
[0029] 3) Add different additives to the ink prepared in step 2) in proportion to reduce the decomposition temperature of the ink and adjust the viscosity and surface tension of the ink. In various configurations, the ink may contain one or more of a viscosity regulator, a surface tension modifier, a film former, a defoamer, or any mixture thereof. Stir at room temperature for 1 to 10 hours until the ink is dissolved without particles to obtain a glass component ink.
[0030] 4) The glass component ink prepared in step 3) is filtered through a 0.22 μm microporous filter membrane to obtain a particle-free glass component ink.
[0031] The process of adding the particle-free glass component ink into the conductive paste as a sintering aid comprises the following steps:
[0032] The prepared ink containing the particle-free glass component is added to different conductive pastes at a volume fraction of 1 to 20%, and stirred for 1 hour to obtain a mixed ink with uniform components. The mixed ink is coated or printed on different substrates by drip coating, dip coating, spin coating or printing to form a layer or pattern, and then sintered by a certain method to obtain a metal film.
[0033] Furthermore, the bismuth precursor in step 1) can be various bismuth-containing organic substances. The optimal ratio of the bismuth precursor is 20-50 wt %. By increasing the amount of the bismuth precursor added, the complexing efficiency of the metal precursor can be improved.
[0034] Further, the solvent in step 1) can be a mixture of one or more organic solvents such as alcohol, ether, ester, etc.; as a solvent, in order to prevent affecting the decomposition temperature of the ink, a solvent with a boiling point below 300°C under normal pressure (one atmosphere) is preferred. The organic solvent can be an aromatic solvent, a non-aromatic solvent, or a mixture of aromatic and non-aromatic solvents. Methanol, ethanol, ethylene glycol, n-propanol, isopropanol, 1.2-butanediol, glycol, diethylene glycol, triethylene glycol, propylene glycol, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, dimethyl adipate, diethyl adipate, dimethyl succinate (butanedioic acid), dimethyl glutarate, DBE, etc. can be listed. The amount of solvent ranges from about 10 to 70wt%.
[0035] Furthermore, the amine complexing agent in step 1) is one or a mixture of ammonia, aliphatic amines, alcohol amines, amides, and aromatic amines. As ligands, 1,2-propylenediamine, ethylenediamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, n-hexylamine, ethanolamine, isopropanolamine, diethylethylenediamine, dihydroxyethylenediamine, and trihydroxyethylenediamine can be listed. Preferably, the amine complexing agent is added in an amount of 10 to 20 wt%.
[0036] Furthermore, the glass component containing boron and silicon in step 2) is various organic substances containing boron and silicon. Such as trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, sodium perborate, silane, polysiloxane, polysilane, ethyl orthosilicate, butyl orthosilicate, tetraphenyl silicate, isoamyl myrosilicate, tetrabenzyl orthosilicate and mixtures thereof. The amount ranges from about 1 to 20 wt %.
[0037] Further, the function of the viscosity modifier in step 3) is mainly to adjust the viscosity of the ink so that the ink is suitable for different conductive pastes. Preferably, the viscosity of the ink can be adjusted to 1-60 mPa·s at room temperature 25°C, such as gums such as gum arabic, pectin, agar, gelatin, alginate, carrageenan, general gelatin, polysaccharide derivatives, etc. Preferred viscosity modifiers also include cellulose polymers, polyacrylates, polystyrene, polyolefins, polyvinyl pyrrolidone, polypyrrolidone, polyvinyl acetal, polyester, polyimide, polyetherimide, polyol, silicone, polyurethane, epoxy resin, phenolic resin, phenol formaldehyde resin, polyalkylene carbonate and mixtures thereof. Preferred organic polymer viscosity modifiers can be homopolymers or copolymers. The amount ranges from about 0.001 to 5wt%.
[0038] Furthermore, the ink in step 3) is affected by different additives, and the viscosity is preferably 10 to 40 mPa·s, and the surface tension is preferably 5 to 40 mN / m.
[0039] Further, in step 3), the defoamer can prevent the formation of foam, reduce or eliminate the original foam. Preferred defoamers can be fluorosilicone, mineral oil, vegetable oil, polysiloxane, ester wax, fatty alcohol, glycerol, stearate, silicone, polypropylene polyether and mixtures thereof. The amount ranges from about 0.001 to 5 wt%.
[0040] Furthermore, in step 5), the printed substrate material is silicon, silicon carbide, quartz, glass, ceramics and various suitable substrates, such as polyethylene terephthalate (PET), polydimethylsiloxane (PDMS), polystyrene, acrylonitrile, butadiene, styrene, polycarbonate, polyimide (e.g. KaptonTM), polyetherimide (e.g. UltemTM), thermoplastic polyurethane (TPU), silicone film, printed circuit board substrate (e.g. FR4), glass, metal, dielectric coating, etc.
[0041] Furthermore, the various film-forming methods mentioned in step 5) include drip coating, coating, spraying, lamination, and suspension coating; the pattern printing method includes screen printing, inkjet printing, roll-to-roll printing, silk screen printing, offset printing, flexographic printing, lithographic printing, gravure printing, stencil spraying, pad printing or any other method.
[0042] Furthermore, in step 5), the conductive paste coating is dried and sintered by heat treatment or laser sintering to form a metal film. The conductive ink can be sintered and cured under an inert atmosphere (such as nitrogen and / or argon), a reducing atmosphere (such as hydrogen), air, or vacuum. The sintering temperature is preferably in the range of 400 to 800° C. and the time is 10 min to 5 h.
[0043] Furthermore, the conductive paste in step 6) is a conductive paste configured with various functional phases. It includes glass-based conductive paste and resin-based conductive paste. According to the classification of the conductive functional phase filler, the conductive paste includes carbon paste (graphite conductor) and various metal pastes, such as gold powder paste, silver powder paste, copper powder paste, silver-plated copper powder paste, nickel powder paste and various modified metal pastes. The volume fraction of the particle-free glass component ink added to the conductive paste is 1 to 20%.
[0044] The present invention is described in more detail below by way of examples, but the scope of the present invention is not limited to these examples. The bismuth isooctanoate, silver oxalate, silver powder, complexing agent, organic additive and solvent used in the examples of the present invention are all commercially available products.
[0045] [Example 1]
[0046] The high-stability particle-free glass component ink is composed of 32% bismuth isopropoxide, 14% 1,2-propylenediamine, 4% ethyl orthosilicate, 4% tributyl borate, 1% epoxy resin and 45% acetone in percentage by mass. The preparation method is as follows:
[0047] According to the above ratio, 1,2-propylenediamine is first mixed with the solvent, and after mixing evenly, bismuth isopropoxide is added to the mixed solution, stirred at room temperature for 3 hours until fully dissolved, then ethyl orthosilicate, tributyl borate and epoxy resin are added and stirred until dissolved, and filtered through a 0.22μm microporous filter membrane to obtain the particle-free glass component ink of the present invention. Its viscosity is 24.63mPa·s and its surface tension is 26.2mN / m; 200μL of the ink is taken and spin-coated on a 2·2cm glass substrate. During the spin-coating process, the spin-coating parameters are set to a uniform coating speed of 500r / min, a uniform coating time of 10s, a spin-coating speed of 1000r / min, and a spin-coating time of 15s. The temperature is raised to 500℃ at a heating rate of 40℃ / min, and sintered for 90min to obtain a glass powder film.
[0048] [Comparative Example 1]
[0049] The high-stability particle-free glass component ink is composed of 32% bismuth isopropoxide, 14% 1,2-propylenediamine, 15% ethyl orthosilicate, 10% tributyl borate, 1% epoxy resin and 28% acetone in mass percentage. The preparation method is as follows:
[0050] According to the above proportions, 1,2-propylenediamine and the solvent are first mixed, and after mixing evenly, bismuth isopropoxide is added to the mixed solution, stirred at room temperature for 3 hours until fully dissolved, and then tetraethyl orthosilicate and epoxy resin are added and stirred to dissolve. After adding tributyl borate, white turbidity is generated during stirring, and white precipitate is deposited at the bottom after standing, and a particle-free ink cannot be formed.
[0051] [Example 2]
[0052] The high-stability particle-free glass component ink is composed of 45% bismuth neodecanoate, 15% ethylamine, 10% tetraphenyl silicate, 5% trimethyl borate, 1% epoxy resin and 24% diethylene glycol ethyl ether in percentage by mass.
[0053] The preparation method is:
[0054] According to the above ratio, ethylamine and solvent are first mixed, and after mixing evenly, bismuth neodecanoate is added to the mixed solution, stirred at room temperature for 3 hours until fully dissolved, tetraphenyl silicate, trimethyl borate and epoxy resin are added and stirred until dissolved, and filtered through a 0.22μm microporous filter membrane to obtain the particle-free glass component ink of the present invention. Its viscosity is 28.72mPa·s and its surface tension is 31.6mN / m; 200μL of the ink is taken and spin-coated on a 2·2cm silicon carbide substrate. During the spin-coating process, the spin-coating parameters are set to a uniform coating speed of 500r / min, a uniform coating time of 10s, a spin-coating speed of 1000r / min, and a spin-coating time of 15s. The temperature is raised to 500℃ at a heating rate of 40℃ / min, and sintered for 90min to obtain a glass powder film.
[0055] [Example 3]
[0056] A high-stability, particle-free glass component ink is used as a sintering aid, and is composed of 40% bismuth isooctanoate, 15% 1,2-propylenediamine, 3% butyl orthosilicate, 5% trimethyl borate, 1% epoxy resin and 36% diethylene glycol ethyl ether in percentage by mass.
[0057] The silver ink is composed of 40% silver oxalate, 21% 1,2-propylenediamine and 39% ethanol in mass percentage, and the volume fraction of the glass component ink added is 9 vol%. The preparation method is:
[0058] According to the above ratio, 1,2-propylenediamine is first mixed with the solvent, and after mixing evenly, bismuth isooctanoate is added to the mixed solution, stirred at room temperature for 3 hours until fully dissolved, then butyl orthosilicate, trimethyl borate and epoxy resin are added and stirred until dissolved, and filtered through a 0.22μm microporous filter membrane to obtain the particle-free glass component ink of the present invention. Then 9vol% of the ink is added to the silver ink and stirred for 1h before filtering to obtain a mixed ink. Take 200μL of the ink and spin coat it on a 2·2cm silicon carbide substrate. During the spin coating process, the spin coating parameters are set to a uniform coating speed of 500r / min, a uniform coating time of 10s, a spin coating speed of 1000r / min, and a spin coating time of 15s. Heat to 500℃ at a heating rate of 40℃ / min, sinter for 90min, and obtain a metal film. The bonding strength between the silver film and the substrate is tested by 3M tape and the results show a 5B grade, with the highest bonding strength of 26MPa.
[0059] [Comparative Example 3]
[0060] The silver ink is composed of 40% silver oxalate, 21% 1,2-propylenediamine and 39% ethanol in percentage by mass, and the particle-free glass component ink of the present invention is not added. The preparation method of the silver ink is as follows:
[0061] According to the above ratio, 1,2-propylenediamine is first mixed with the solvent, and after mixing evenly, the silver oxalate precursor is added to the mixed solution, stirred at room temperature for 3 hours until fully dissolved, and filtered through a 0.22μm microporous filter membrane to obtain the particle-free glass component ink of the present invention. Take 200μL of the ink and spin-coat it on a 2·2cm silicon carbide substrate. During the spin coating process, the spin coating parameters are set to a uniform coating speed of 500r / min, a uniform coating time of 10s, a spin coating speed of 1000r / min, and a spin coating time of 15s. Heat to 500℃ at a heating rate of 40℃ / min, sinter for 90min, and obtain a metal film. The bonding strength between the silver film and the substrate is tested by 3M tape and the results show that it is only grade 3B.
[0062] [Example 4]
[0063] High-stability particle-free glass component ink is used as a sintering aid, and is composed of 40% bismuth isooctanoate, 15% 1,2-propylenediamine, 5% ethyl orthosilicate, 5% trimethyl borate, 1% epoxy resin and 34% diethylene glycol ethyl ether by mass percentage. The conductive silver paste is prepared by mixing 65% commercially available silver powder, 14% isopropyl alcohol, 7% ethylene glycol and 14% pinene alcohol by mass percentage. The volume fractions of the glass component ink added are 6vol%, 9vol%, and 12vol%, and are numbered S1, S2 and S3 respectively. The preparation method is:
[0064] According to the above ratio, 1,2-propylenediamine is first mixed with the solvent, and after mixing evenly, bismuth isooctanoate is added to the mixed solution, stirred at room temperature for 3h until fully dissolved, and then ethyl orthosilicate, trimethyl borate and epoxy resin are added and stirred until dissolved, and the particle-free ink of the present invention is obtained after filtering through a 0.22μm microporous filter membrane. Then take the ink and add it to the conductive silver paste and stir and mix to obtain a mixed ink. Take 200μL of the ink and spin coat it on a 2·2cm silicon carbide substrate. During the spin coating process, the spin coating parameters are set to a uniform coating speed of 500r / min, a uniform coating time of 10s, a spin coating speed of 1000r / min, and a spin coating time of 15s. Heat to 500℃ at a heating rate of 40℃ / min, sinter for 90min, and obtain a metal film. Through testing, the shear strength of the ink with a glass component ink addition amount of 12vol% is increased from 23MPa to 43.6MPa.
Claims
1. A particle-free glass component ink for use in conductive paste / ink, characterized in that: The particle-free glass component ink uses a bismuth precursor component and an amine complexing agent to form a stable complex, then adds a glass component containing silicon and boron, dissolves it in an organic solvent and filters it to form a particle-free ink, and then adds it to a traditional conductive paste as a sintering aid; the particle-free glass component ink decomposes in situ during sintering to produce bismuth oxide, boron oxide, and silicon oxide, which are filled between metal particles and between the metal and the substrate, become molten during further heating, and produce dense ohmic contact after cooling and solidification.
2. The particle-free glass component ink for conductive paste / ink according to claim 1, characterized in that: Additives are added to the particle-free glass component ink to adjust its viscosity and leveling properties and adjust the glass phase transition temperature after the glass phase components are decomposed.
3. The particle-free glass component ink for conductive paste / ink according to claim 1 or 2, characterized in that: The particle-free glass powder ink has strong stability and no precipitation is generated when stored at room temperature for one month.
4. A method for preparing a particle-free glass component ink for use in conductive paste / ink as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: 1) The particle-free glass component ink is composed of the following components in percentage by mass: 20-50% bismuth precursor component, 1-20% boron and silicon-containing glass component, 10-20% amine complexing agent and 0.001-10% organic additive, and the rest is solvent; the amine complexing agent is fully dissolved in the solvent according to the above proportion, and then the bismuth precursor is added and stirred until completely dissolved to prepare a basic bismuth-based ink; 2) adding a glass component containing boron and silicon to the bismuth-based ink prepared in step 1), and stirring at room temperature until the bismuth is completely dissolved; 3) adding different additives to the ink prepared in step 2) in proportion to reduce the decomposition temperature of the ink and adjust the viscosity and surface tension of the ink; in various configurations, the additives are one or more of a viscosity regulator, a surface tension modifier, a film former, and a defoaming agent; stirring at room temperature for 1 to 10 hours until the ink is dissolved without particles, to obtain a glass component ink; 4) The glass component ink prepared in step 3) is filtered through a 0.22 μm microporous filter membrane to obtain a particle-free glass component ink.
5. The preparation method according to claim 4, characterized in that: The bismuth precursor is various bismuth-containing organic substances; the solvent is a mixture of one or more organic solvents with a boiling point below 300° C. under normal pressure; the amine complexing agent is one or more of ammonia water, aliphatic amines, alcohol amines, amides, and aromatic amines; and the boron- and silicon-containing glass component is various boron- and silicon-containing organic substances.
6. The preparation method according to claim 4, characterized in that: The viscosity regulator is gum arabic, pectin, agar, gelatin, alginate, carrageenan, general gelatin or a polysaccharide derivative; the organic polymer viscosity regulator is a homopolymer or a copolymer; the defoaming agent is one or more of fluorosilicone, mineral oil, vegetable oil, polysiloxane, ester wax, fatty alcohol, glycerin, stearate, silicone and polypropylene polyether.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The ink is affected by different additives, and has a viscosity of 10 to 40 mPa·s and a surface tension of 5 to 40 mN / m.
8. An application of the particle-free glass component ink for conductive paste / ink as claimed in any one of claims 1 to 3 and the particle-free glass component ink for conductive paste / ink prepared by the preparation method as claimed in any one of claims 4 to 7, characterized in that: The particle-free glass component ink is added to the conductive paste as a sintering aid; The prepared ink containing the particle-free glass component is added to different conductive pastes at a volume fraction of 1 to 20%, and stirred for 1 hour to obtain a mixed ink with uniform components; the mixed ink is coated or printed on different substrates by dripping, dipping, spin coating or printing to form a layer or pattern, and it is sintered by a certain method to obtain a metal film.
9. The use of the particle-free glass component ink according to claim 8, characterized in that: The substrate material is silicon, silicon carbide, quartz, glass, and ceramics; the sintering temperature ranges from 400 to 800° C., and the sintering time ranges from 10 minutes to 5 hours.
10. The use of the particle-free glass component ink according to claim 8 or 9, characterized in that: The conductive paste includes glass-based conductive paste and resin-based conductive paste; according to the classification of conductive functional phase fillers, the conductive paste includes carbon paste and various metal pastes.
Citation Information
Patent Citations
Method for preparing electrode silver paste for environment-friendly semiconductor capacitor
CN102157221A
Silver conductive ink and method for manufacturing printed circuit with same
CN103517569A
Submicron bismuth silicate powder for glass printing ink and preparation method
CN105084375A
Silver-aluminum paste used for solar cell
CN105810759A
Method for preparing bismuth-boron-based flexible catalytic electrode in organic phase
CN113832491A